SPK PENENTUAN SISWA PENERIMA BEASISWA MALAKA CERDAS MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - molo, ana (JATISI, 2024)
This research focuses on developing a decision support system for determining scholarship recipient students at SD Impres Abat Bot using the Simple Additive Weighting (SAW) method. The background to this research is the need for an efficient and objective system in the scholarship recipient selection process, which has been done manually and takes time. The aim of this research is to build and implement a SAW-based decision support system, as well as evaluate the optimality of the recommendation results. The methods used in this research include interviews, observation and literature study. System development follows the waterfall method which consists of analysis, design, coding and testing stages. This system is designed to consider various criteria that have been applied by SDI Abat Bot in determining scholarship recipients. The research results show that the application of the SAW method in a decision support system can provide optimal, fair and transparent recommendation results. It is hoped that this system can help schools make more objective decisions regarding scholarship awards, as well as become a reference for further research in the same field. Keywords— Determination, Decision Support Systems, Simple Additive Weighting (Saw), Scholarship